European Science Diplomacy in the Southern Neighbourhood: Insights from Morocco and Tunisia - Šime, Zane (Politologija, 2024)
The resilience-building in the European Southern Neighbourhood benefits from access to research-intense solutions developed by and in collaboration with centres of competence located across Europe. Data-set observations retrieved from ‘Community Research and Development Information Service’ (CORDIS) indicate that despite the overall propensity towards establishing relational ties with Horizon 2020 project coordinators located in the European Mediterranean littoral countries, Morocco and Tunisia, profited from exposure to the thematically diverse and geographically dispersed expertise hosted by the European Research Area. Practice theory with a focus on the field and process tracing provide a good basis for analysing past research interlinks that offer some limited, yet valuable insights into the implicit European science diplomacy routines, including examples that support the positioning of France, Spain, especially Barcelona, as explicit science diplomacy hubs.
Keywords: science diplomacy; practice theory; Horizon 2020; research cooperation; European Research Area; European Southern Neighbourhood